2022
DOI: 10.1187/cbe.21-05-0131
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Emotions, Perceived Coping, and Outcomes in Response to Research-Based Challenges and Failures in Two Sequential CUREs

Abstract: This study examines students’ experiences with research challenges and failures in the context of two sequential research-based courses. As a result of experiencing challenges and failures, students experience negative emotions. Yet, when provided time to iterate, they respond with adaptive coping behaviors and report positive outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…This ability to collaborate within a group and between groups helped bring multiple minds together to address obstacles encountered by individuals, groups, and the overall research project. Exposure to potential failure with research is simultaneously a goal of the CURE and a potential obstacle. , The faculty in this study kept the students motivated with positive reinforcement and reassurance that evaluation was based on participation in the process, not the results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability to collaborate within a group and between groups helped bring multiple minds together to address obstacles encountered by individuals, groups, and the overall research project. Exposure to potential failure with research is simultaneously a goal of the CURE and a potential obstacle. , The faculty in this study kept the students motivated with positive reinforcement and reassurance that evaluation was based on participation in the process, not the results.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to potential failure with research is simultaneously a goal of the CURE and a potential obstacle. 12,41 The faculty in this study kept the students motivated with positive reinforcement and reassurance that evaluation was based on participation in the process, not the results.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This may be an indication that CURE GTAs, like inquiry GTAs, have difficulty in providing space for students to learn through struggle [ 67 ]. Recent work has found that experiences of “failure” and challenges in a CURE can be beneficial, and can increase student buy-in, resiliency in navigating obstacles, and understanding of the nature of science [ 20 , 68 , 69 ]. Yet, these studies on the benefits of failure and facing challenges during a CURE all highlighted the importance of psychosocial support from the instructor in order to help students understand and learn from these experiences[ 20 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has found that experiences of “failure” and challenges in a CURE can be beneficial, and can increase student buy-in, resiliency in navigating obstacles, and understanding of the nature of science [ 20 , 68 , 69 ]. Yet, these studies on the benefits of failure and facing challenges during a CURE all highlighted the importance of psychosocial support from the instructor in order to help students understand and learn from these experiences[ 20 , 68 , 69 ]. Further, instructor actions and dispositions are thought to be a key part to supporting students to develop adaptive coping behaviors in response to the challenges and failures they encounter in their learning environments[ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, relevant to promoting newcomer engagement is coping with the experiences of failure and frustration that are inherent to authentic inquiry (Corwin et al, 2022; Goodwin et al, 2021). The way a mentor supports a learner through the emotional aspects of scientific inquiry may influence a learner's motivation to persist through these challenges (Pfund et al, 2016).…”
Section: Introductionmentioning
confidence: 99%